Perineural Injection for Treatment of Root-Signature Signs Associated with Lateralized Disk Material in Five Dogs (2009–2013) - Giambuzzi, Sarah; Pancotto, Theresa; Ruth, Jeffrey (Frontiers in Veterinary Science, 2016)
Intervertebral disc disease is common in dogs; cervical IVDD accounts for 13-25% of all cases. Surgical interventions provide access to ventrally displaced disc material, however procedures to remove dorsally or laterally displaced material are more difficult and traumatic. This case series examines the clinical efficacy and safety of perineural injection as an alternative treatment option for dogs experiencing root signature signs associated with lateralized disc material in the cervical spine. Dogs in this study were part of the normal patient population in which advanced imaging modalities were used to identify lateralized disc material. Patients, under anesthesia, underwent fluoroscopically guided perineural injection of methylprednisolone +/- bupivacaine. All patients experienced improvement in root-signature signs and some remained pain free without the assistance of oral pain medication. These findings suggest the perineural injection of methylprednisolone +/- bupivacaine represents a viable option for dogs with cervical lateralized disc material causing root-signature signs.